Animal welfare aspects in respect of the slaughter or killing of pregnant livestock animals (cattle, pigs, sheep, goats, horses). (30th May 2017) - ,; More, Simon; Bicout, Dominique; Botner, Anette; Butterworth, Andrew; Calistri, Paolo; Depner, Klaus; Edwards, Sandra; Garin‐Bastuji, Bruno; Good, Margaret; Gortazar Schmidt, Christian; Michel, Virginie; et al.
Abstract: This scientific opinion addresses animal welfare aspects of slaughtering of livestock pregnant animals. Term of Reference (ToR) 1 requested assessment of the prevalence of animals slaughtered in a critical developmental stage of gestation when the livestock fetuses might experience negative affect. Limited data on European prevalence and related uncertainties necessitated a structured expert knowledge elicitation (EKE) exercise. Estimated median percentages of animals slaughtered in the last third of gestation are 3%, 1.5%, 0.5%, 0.8% and 0.2% (dairy cows, beef cattle, pigs, sheep and goats, respectively). Pregnant animals may be sent for slaughter for health, welfare, management and economic reasons (ToR2); there are also reasons for farmers not knowing that animals sent for slaughter are pregnant. Measures to reduce the incidence are listed. ToR3 asked whether livestock fetuses can experience pain and other negative affect. The available literature was reviewed and, at a second multidisciplinary EKE meeting, judgements and uncertainty were elicited. It is concluded that livestock fetuses in the last third of gestation have the anatomical and neurophysiological structures required to experience negative affect (with 90–100% likelihood). However, there are two different possibilities whether they perceive negative affect. It is more probable that the neurophysiological situation does not allow for conscious perception (with 66–99% likelihood) because of brain inhibitory mechanisms. There is also a less probable situation that livestock fetuses can experience negative affect (with 1–33% likelihood) arising from differences in the interpretation of the fetal electroencephalogram, observed responses to external stimuli and the possibility of fetal learning. Regarding methods to stun and kill livestock fetuses at slaughter (ToR4), sets of scenarios and respective actions take account of both the probable and less probable situation regarding fetal ability for conscious perception. Finally, information was collated on methods to establish the dam's gestational stage based on physical features of livestock fetuses (ToR5).